2012
DOI: 10.1051/kmae/2013034
|View full text |Cite
|
Sign up to set email alerts
|

Invasive crayfish increase habitat connectivity: a case study in a large boreal lake

Abstract: Key-words:crayfish, habitat connectivity, invasive species, stable isotopes Several studies have shown that distinct compartments of lake ecosystems are coupled via transportation of organic matter, nutrients and energy across habitat boundaries. Here we evaluate the potential of the invasive signal crayfish (Pacifastacus leniusculus (Dana)) to modify energy pathways in large boreal lakes. Using a stable isotope mixing model and calculation of the isotopic niches we estimated the contribution of different food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 55 publications
3
20
1
Order By: Relevance
“…This was mainly due to the 13 Cc range of some lakes where crayfish C signatures indicated wider variation and thus a wider trophic niche. Ruokonen et al (2012) found that individual signal crayfish caught from the littoral in large Lake Päijänne had smaller trophic niche than those sampled from the profundal. Lake Iso-Tarus, which had the largest crayfish C signature range of the study lakes (I), registered low values of sublittoral macroinvertebrate abundance and species richness (III), but among the highest in the littoral, whereas signal crayfish lakes with the smallest crayfish carbon signature range, like lakes Ala-Karkijärvi and Syväjärvi, exhibited an opposite pattern.…”
Section: Stable Isotopes and Food Sources (I)mentioning
confidence: 84%
See 2 more Smart Citations
“…This was mainly due to the 13 Cc range of some lakes where crayfish C signatures indicated wider variation and thus a wider trophic niche. Ruokonen et al (2012) found that individual signal crayfish caught from the littoral in large Lake Päijänne had smaller trophic niche than those sampled from the profundal. Lake Iso-Tarus, which had the largest crayfish C signature range of the study lakes (I), registered low values of sublittoral macroinvertebrate abundance and species richness (III), but among the highest in the littoral, whereas signal crayfish lakes with the smallest crayfish carbon signature range, like lakes Ala-Karkijärvi and Syväjärvi, exhibited an opposite pattern.…”
Section: Stable Isotopes and Food Sources (I)mentioning
confidence: 84%
“…Invertebrate grazers were greatly reduced by crayfish, and indirectly periphyton was positively affected by crayfish. Previous studies reported that invasive crayfish species can also affect littoral benthic fishes (Guan andWiles 1997, Hirsch andFischer 2008), although recent findings (Ruokonen et al 2012) have demonstrated the contrary. Moreover, invasive crayfish represent a severe threat to their native counterparts and in the majority of cases outcompete and replace native species (Nyström et al 2001, Stenroth and Nyström 2003, Bubb et al 2006.…”
Section: Crayfish and Their Ecological Effectsmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, the studies of Semmens et al (2009), Wootton (2012, Cummings & Schindler (2013), and Silva-Costa & Bugoni (2013) explored the contributions of marine and freshwater or terrestrial resources to consumers in spatially subsidized food webs (Polis et al 1997). Jensen et al (2012), Xu et al (2012), and Ruokonen et al (2012) studied benthic−pelagic or benthic−terrestrial systems. However, studying ecotones does not guarantee a well-resolved resource polygon, as many ecotonal food webs were actually poorly resolved.…”
Section: Discussionmentioning
confidence: 99%
“…SIA has increasingly been used in ecological studies focusing on crayfishes (e.g. Stenroth et al, 2005, Roth et al, 2006Ruokonen et al, 2012;Ercoli et al, 2013;Jackson et al, 2014), which motivated this investigation on how these methods could be applied to specific laboratory conditions and diets. The main aims of our study were 1) to define, under experimental nutritional treatment, the temporal dynamics of the stable isotope ratios in two freshwater crayfishes, the noble crayfish (Astacus astacus, Linné) and the signal crayfish (Pacifastacus leniusculus, Dana), and 2) to assess the effect of controlled, single food type diet on the condition of crayfish.…”
Section: Introductionmentioning
confidence: 99%